Electronic Accounting Information Systems in Providing Cash Budget and Supply Chain Management - Koshan, Hayder Matloob (Opción, 2019)
This research has been developed for the purpose of explaining the effect of the use of electronic accounting information systems and their role in preparing cash budget and supply chain management via exploratory descriptive method, reviewing the supply chain literature. Studies have also shown that factors such as the breadth of the organization, the degree of success, uncertainty and pressure of other chain partners play an important role in the adoption of information technology. In conclusion, fast, accurate and timely access to financial information is a key criterion for the development of organizations, including government agencies.